ETIOLOGICAL CHARACTERIZATION AND COMPLICATIONS OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN - S.P. Kokoreva; L.A. Sakharova; N.P. Kuprina ("Paediatrician" Publishers LLC, 2008)
Etiology of acute respiratory infections (ARI) and their complications of 220 children were examined. Fluorescent antibody method, hemagglutinationbinhibition reaction, enzyme immunoas say and bacteriological study were used for the examination. ARI etiology was rendered more precise in 147 children. It was demonstrated that over a half of infectious diseases of respiratory tract take course as mixed infection (combination of respiratory, herpetic viruses and intracellular parasites), and with account of bacterial flora, over 80 per cent. ARI in children of mixed etiology are 1,7 times more often concurrent with complicated forms of disease. The appropriateness of including Arbidol into the medical regimen of children with ARI is examined. Key words: children, acute respiratory infections, etiology, complications, treatment, arbidol.